Comprehensive associations between pearl oyster beds and coral, seagrass, and algal habitats in the hottest sea on the planet - AlMealla, Reem K.; Edullantes, Brisneve; Ali, Mohamed; Mardhi, Zainab; Khan, Manaal; Sharif, Mominah; Tyabji, Ayesha; AlMousa, Nada; Omran, Fatima; Hasan, Mariam; Hazeem, Layla; Khamis, Ahmed S.; et al. (Frontiers in Marine Science, 2025)
IntroductionPearl oyster ecosystems have played a central role in Bahrain’s marine economy and cultural heritage for centuries. Despite their ecological importance, systematic research on Bahrain’s pearl oyster beds is lacking since the early 1990s. In this study a detailed assessment of the benthic composition, pearl oyster community structure, population size, and pearl yield on pearl oyster beds is provided for Bahraini waters.MethodsBetween January and May 2024, field surveys were conducted at ten sites across Bahrain’s northern, eastern, and western waters to assess benthic composition, pearl oyster community structure, population size structure, and pearl yield. A total of 1,973 pearl oysters were collected and studied.ResultsNine species of pearl oysters were recorded, with Pinctada radiata dominating across all sites. Pinctada species richness was highest in the north (six species) with greater oyster densities (34 ± 4.9 oysters/m2) compared to the east (6 ± 2.7 oysters/m2) and west (10 ± 2.9 oysters/m2). Oyster beds were associated with coral in the north (up to 22.6 ± 2.3% cover), algae in the upper eastern (75.6% ± 4.4%) and western (65.8% ± 4.2%) sites, and seagrass mixed with algae in the lower eastern (27.9% ± 4.9% seagrass) and western (33.1% ± 4.2% seagrass) sites. Pearl yield was highest in the Northern and western sites, with Hayr Bu Amamah (14.3%) and Hayr Bul Thamah (11.1%) showing the highest incidence of pearls.Discussion/ConclusionThis study provides the first comprehensive quantitative assessment of Bahrain’s pearl oyster beds in over three decades. Given that these oyster beds inhabit some of the most extreme marine environments on the planet, where temperatures fluctuate annually between 16 °C to 36 °C and salinity exceed 50 ppt in certain areas. These findings provide critical baseline data to inform sustainable management, conservation planning and marine heritage protection in Bahrain and the wider Gulf region.